If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 5y = 9y Combine like terms: 3y + 5y = 8y 8y = 9y Solving 8y = 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. 8y + -9y = 9y + -9y Combine like terms: 8y + -9y = -1y -1y = 9y + -9y Combine like terms: 9y + -9y = 0 -1y = 0 Divide each side by '-1'. y = 0 Simplifying y = 0
| m^2+9m+7=-5+9(-5)+7 | | 5x^2+10x=40 | | w^2+7w=8 | | 2w^2+6w=8 | | 4x^2=-9x-5 | | 3a^2+a+20=0 | | 3a^2+7a+20=0 | | 11-7-x=79-21x | | x^2=4x-21 | | w^2-14w+49= | | 15c^2+23c-28=0 | | 4x+15y=7000 | | 4x^2+8x-192=0 | | 12m+8=24 | | 15z^2-16z=-4 | | 32c^2-20c+24c-15=0 | | 2(3x+9)=7x+80 | | 5x^2+12x=-4 | | 2z^2-13z=-21 | | x^2+7x+13=1 | | 5x^2+37x=-14 | | 15x^2+37x=14 | | 0.7(4x+0.3)=41.65 | | 2w^2+3w=27 | | 16x-4=4(2x-3) | | 0.4(d-3.5)=1.12 | | -2x^2-16x+40= | | 0.58n-0.86=4.592 | | 3y^2-y=24 | | 2.25x+2.56(450-x)=1143 | | -4u-22=2(u+1) | | 16x-2y=74 |